Beyond Business: How Parenting Style Shapes Succession Planning and Success in Family Firms - Hidayati, Aprihatiningrum; Rofi, M Akhsanur (JMK (Jurnal Manajemen dan Kewirausahaan), 2026)
Purpose This study examines the pivotal role of parenting styles—authoritative, authoritarian, and permissive—in shaping succession planning and enhancing succession success in family businesses. It bridges family systems theory and succession management by investigating how family dynamics influence leadership transition effectiveness. Design/methodology/approach Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study analyzes survey data from 210 respondents representing multiple generational cohorts in family enterprises. The model tests both direct and mediating effects among parenting style, succession planning, and succession success. Findings The results indicate that parenting styles and succession planning positively and affect succession success. Moreover, succession planning mediates the relationship between parenting style and business continuity. The model explains 20.7% of the variance in succession success and 14.3% in succession planning, with Q² values (0.137–0.215) showing small-to-moderate predictive relevance. Research limitations/implications Although the explanatory power is moderate, the model demonstrates theoretical robustness and extends family business literature by integrating affective (soft) and procedural (hard) factors in succession. Practical implications Findings offer actionable guidance for family business owners, consultants, and policymakers to develop holistic succession frameworks that combine strategic planning with parental engagement and mentoring. Originality/value This study contributes a novel perspective by demonstrating that successful succession is not merely a managerial process but a relational journey, emphasizing the synergy between parenting behavior and succession management practices for intergenerational continuity. Keywords: family business; family dynamics; parenting style; succession plan; successful succession.